A fast route to obtain modified tin oxide aerogels using hydroxostannate precursors - Beier, Max Gregor; Ziegler, Christoph; Wegner, Karl; Benad, Albrecht; Simon, Frank; Kaskel, Stefan; Eychmueller, Alexander (Materials Chemistry Frontiers, 2018)
Nanostructured tin oxide materials with a high specific surface area and porosity are promising for applications such as electrocatalysis, lithium ion batteries or sensors. Here, we present a facile strategy for the synthesis of tin oxide aerogels using inexpensive hexahydroxostannate as a tin precursor. This easy and scalable method yields tin oxide aerogels with a high specific surface area and a wide pore size distribution. The method can be modified by adding hexahydroxoantimonate to obtain antimony-doped tin oxide aerogels that exhibit electrical conductivity after annealing. Cogelation with other preformed nanoparticles (e.g. Au, Pt) leads to mixed gels. Both modifications do not have a large impact on the porous properties of the obtained aerogels. Tin oxide materials prepared via this route can be tailored to a specific application by versatile modification possibilities.
CRIS-Team Scopus Importer:2022-04-14